Signatures of confinement in Landau gauge QCD - Pawlowski, Jan M.; Litim, Daniel F. (Arxiv, 2004)
We summarise an analysis of the infrared regime of Landau gauge QCD by means of a flow equation approach. The infrared behaviour of gluon and ghost propagators is evaluated. The results provide further evidence for the Kugo-Ojima confinement scenario. We also discuss their relation to results obtained with other functional methods as well as the lattice.
Gesehen am 06.12.2017